2017
DOI: 10.1038/s41598-017-13233-2
|View full text |Cite
|
Sign up to set email alerts
|

R/G editing in GluA2Rflop modulates the functional difference between GluA1 flip and flop variants in GluA1/2R heteromeric channels

Abstract: In α-amino-3-hydroxy-5-methyl-4-isoxazole-propionate (AMPA) receptors, RNA editing and alternative splicing generate sequence variants, and those variants, as in GluA2-4 AMPA receptor subunits, generally show different properties. Yet, earlier studies have shown that the alternatively spliced, flip and flop variants of GluA1 AMPA receptor subunit exhibit no functional difference in homomeric channel form. Using a laser-pulse photolysis technique, combined with whole-cell recording, we measured the rate of chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 83 publications
(135 reference statements)
3
14
0
Order By: Relevance
“…This assumption was consistent with our observation that the whole-cell current rise followed a first-order rate law (Eq. 2) in the entire range of glutamate concentrations not only in this study but also in all of our previous studies of other AMPA receptors 29,30,4853 .…”
Section: Methodssupporting
confidence: 80%
“…This assumption was consistent with our observation that the whole-cell current rise followed a first-order rate law (Eq. 2) in the entire range of glutamate concentrations not only in this study but also in all of our previous studies of other AMPA receptors 29,30,4853 .…”
Section: Methodssupporting
confidence: 80%
“…For them, both flip and flop splice isoforms with R/G editing were identified (Table ). It was recently shown that this type of editing accelerated opening and desensitization of GRIA2‐formed ion channels, at least for flop isoforms . The better recognized Q/R editing site on GRIA2, which was shown to be completely edited in adult brains, was also identified with lesser spectral counts than the R/G site, most likely due to the chemical properties of the corresponding peptide.…”
Section: Resultsmentioning
confidence: 99%
“…For proteins, the main instrument was to create recombinant, forcibly edited receptors in cell and organism models. With targeted proteomics based on our findings, one can monitor dynamics of the edited isoform in intact tissues, including clinical samples …”
Section: Resultsmentioning
confidence: 99%
“…Editing of this site is extensively growing at each phase of life cycle, presumably illustrating its functional importance. This type of substitution from RNA editing changes the size and electrostatic charge of a residue and was shown to modulate their electrophysiological properties for rat glutamate channel subunits [52].…”
Section: Quantitation Of Brain-specific Edited Proteins During a Fruit Fly Life Cyclementioning
confidence: 99%